2017
DOI: 10.1007/s13312-017-1111-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcome of children with congenital hypothyroidism diagnosed in a national screening program in Turkey

Abstract: Some children with congenital hypothyrodism may have mild to moderate neurodevelopmental retardation, despite the early diagnosis and treatment, and thus need to be under regular follow-up for neurodevelopmental status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
1
5
0
6
Order By: Relevance
“…This was shown in a recent study in 30 such children aged at least 6 years, who demonstrated multiple brain white matter lesions, which correlated with deficits in language development [60]. A study from Turkey showed mild-to-moderate developmental delay at age 2-3 years in early-diagnosed and treated children with congenital hypothyroidism [61]. Ten-year old children with congenital hypothyroidism who were diagnosed via neonatal screening have been shown to be at risk of reduced health-related quality of life (HRQoL), and adverse perception of self-worth, compared with their euthyroid peers [62].…”
Section: Congenital or Overt Hypothyroidismmentioning
confidence: 80%
“…This was shown in a recent study in 30 such children aged at least 6 years, who demonstrated multiple brain white matter lesions, which correlated with deficits in language development [60]. A study from Turkey showed mild-to-moderate developmental delay at age 2-3 years in early-diagnosed and treated children with congenital hypothyroidism [61]. Ten-year old children with congenital hypothyroidism who were diagnosed via neonatal screening have been shown to be at risk of reduced health-related quality of life (HRQoL), and adverse perception of self-worth, compared with their euthyroid peers [62].…”
Section: Congenital or Overt Hypothyroidismmentioning
confidence: 80%
“…The incidence of congenital hypothyroidism varies from country to country, the low incidence of this pathology in developing countries [12,13] may change with systematic screening. Early detection and management of congenital hypothyroidism may also reduce complications, especially mental and intellectual retardation [14][15][16]. Early treatment should be started during the first two weeks of life to have good results [17].…”
Section: Discussionmentioning
confidence: 99%
“…Çok düşük doğum ağırlıklı (ÇDDA<1500 g) bebeklerde tiroksin (T4) düzeyleri yenidoğanın olumsuz sonuçları (ölüm, intraventriküler kanama, periventriküler lökomalazi, serebral palsi) ile ilişkilidir (8). Ayrıca uzun dönemde konjenital hipotiroidinin (KH) nörogelişimsel sonuçlara olumsuz etkisi olduğu bilinmektedir (9,10). Geç prematüre (GH 34-36 hafta arası) bebeklerde hormonları ile solunum desteği arasında ilişki olmadığı rapor edilmiştir.…”
Section: Introductionunclassified